(untitled) (Training and Practice : Journal of Educational Sciences, 2020)
In agreement with the spirit of the era teachers and experts with a vocation need to make an attempt to develop and continually improve their existing expertise in order to increase the efficiency of education and care. It is a well-known fact that preschool years mean the most sensitive period to establish and deepen the competences supporting life-long learning. With regard to the development and maturation of the nervous system the supporting environment, the motivating educational activities create favourable conditions for the learning process of small children. All this helps to build the neural links, to intensify the nervous paths. The main direction of the micro research presented in the study was appointed by important questions to be resolved, that is what level of neuropedagogical expertise kindergarten teachers possess and how and to what extent they use their knowledge in this field to support early childhood brain development.